2004
DOI: 10.1183/09031936.04.00092004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and pharmacotherapy of severe acute respiratory syndrome: what have we learnt?

Abstract: In 2003, the onset of severe acute respiratory syndrome (SARS) caused worldwide chaos. Although SARS was eradicated by isolation towards the end of 2003, sporadic cases have been reported in Singapore, Taiwan and mainland China.In this review, SARS is discussed as a disease, as well as its diagnosis, management and pharmacotherapy.Respiratory physicians and healthcare professionals have to be aware of advances in the understanding of the diagnosis and management of severe acute respiratory syndrome. More resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Critical-illness-associated polyneuropathy/myopathy has also been observed in a few SARS survivors [147]. The reported incidence rates of avascular necrosis of bone among different cohorts in Hong Kong range from 4.7-15 % [124,148,149], whereas one study from Beijing reported a high incidence of 42 % [123].…”
Section: Long-term Outcomementioning
confidence: 94%
“…Critical-illness-associated polyneuropathy/myopathy has also been observed in a few SARS survivors [147]. The reported incidence rates of avascular necrosis of bone among different cohorts in Hong Kong range from 4.7-15 % [124,148,149], whereas one study from Beijing reported a high incidence of 42 % [123].…”
Section: Long-term Outcomementioning
confidence: 94%
“…At fever onset, 80% of SARS patients have airspace consolidation, especially peripheral and lower zone in distribution, on their chest radiographs Tsang et al, 2004). Generally, rapid deterioration of ground-glass consolidation occurs in the first 3 days, peaking between 8 and 10 days after onset of fever to become multilobar and bilateral (Figure 1).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…153,154 Critical illness associated polyneuropathy/mypoathy was also observed in a few SARS survivors. 155 The reported incidence rates of avascular necrosis of bone among different cohorts in HK ranged from 4.7% to 15%, 156,157 whereas 1 study from Beijing reported a high incidence of 42%. 133 Several other groups have shown that persistent lung function abnormalities occur in less than one-third of patients at 1 year and that there was significant impairment of health status among SARS survivors and their carers.…”
Section: Short-termmentioning
confidence: 99%